Facial profile assessment after oral rehabilitation with complete dentures through stereophotogrammetry - Pucciarelli, Maria Giulia Rezende (2022)
Facial collapse is associated with edentulism. Conventional complete dentures (CCD) and implant-supported complete dentures (ISCD) restore facial proportions to the natural appearance. The knowledge about this topic could provide new parameters and metrics based on comprehensive data of the face once these facial changes are unclear. Evaluate the facial esthetic effects of complete dentures treatment through a 3D analysis of the lower third of the face (surface and volume) linear and angular measurements. Also, to assess the facial collapse from tooth loss compared with a control group and quantify whether the two types of rehabilitation (CCD and ISCD) can restore the facial proportions to match those of a dentate patient. The facial analysis was performed through stereophotogrammetry (3D) with the VECTRA H1 device. Linear, angular, and surface measurements were analyzed in the face. The sample was composed with a minimum of 28 patients per group into a control group and the rehabilitated patients with CCD and ISCD. The statistical analysis was performed by an independent t test, paired t-test, and one-way ANOVA, according to the situation analyzed (=0.05 for all analyses). The facial profiles of the edentulous group with and without complete dentures were statistically difference (P.05) in linear and angular measurements. After quantifying the facial collapse by comparing edentulous individuals without complete dentures and the control dentate group, the results showed that the majority of differences occurred in the middle and lower third of the face, evidencing shortening in these areas with differences in facial measures of around 2 to 5 mm less in the edentulous group. The comparison among the two types of rehabilitation (CCD and ISCD) and the dentate patients showed several differences. The ISCD presented no statistical differences with the dentate people. Tooth loss affected the facial proportions in the lower third of the face. The provision of CCD restored their facial appearance but not precisely to the facial proportions of individuals with a natural dentition as the ISCD promoted.